2020
DOI: 10.1038/s41598-020-71769-2
|View full text |Cite|
|
Sign up to set email alerts
|

Transition metals induce control of enhanced NLO properties of functionalized organometallic complexes under laser modulations

Abstract: The molecular engineering of organometallic complexes has recently attracted renewed interest on account of their potential technological applications for optoelectronics in general and optical data storage. The transition metal which induces control of enhanced nonlinear optical properties of functionalized organometallic complexes versus not only the intensity but also the polarization of the incident laser beam is original and important for all optical switching. This makes organometallic complexes valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 71 publications
0
19
0
3
Order By: Relevance
“…They observed that these inorganic aromatic Robin–Day-type superalkali electrides have high sensitivity for use in multistate nonlinear optical switches . The design and synthesis of organic and inorganic electrides continues because of their applications in catalysis, metal-ion batteries, NLO materials, and so forth Recently, transition-metal-based organometallics have been reported to exhibit a better second-harmonic generation (SHG) response. …”
Section: Introductionmentioning
confidence: 99%
“…They observed that these inorganic aromatic Robin–Day-type superalkali electrides have high sensitivity for use in multistate nonlinear optical switches . The design and synthesis of organic and inorganic electrides continues because of their applications in catalysis, metal-ion batteries, NLO materials, and so forth Recently, transition-metal-based organometallics have been reported to exhibit a better second-harmonic generation (SHG) response. …”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear Optical (NLO) materials have progressed gradually over the past 20 years with notwithstanding an ongoing intensive research in view of discovering new NLO materials 1 3 . Such a research of novel NLO materials is driven by the pressing ICT related technological photonics applications, particularly in logic systems, all optical switching, frequency conversion, light amplification, optical bistability, all optical switching among others.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, it can occur in any crystalline material with or without inversion symmetry. However, the SHG behavior has been investigated intensively in coordination compounds (CCs) for the past 20 years, while the THG process in these materials was much less explored . One of the main reasons is that most of the THG processes are usually weak and not easily detected .…”
Section: Introductionmentioning
confidence: 99%